Ecofeminism Movement Through Household Waste Management In The Zona Bening Community, Batu City- East Java - Fitri Yasin; Vina Salviana Darvina S; Su’adah Su’adah (Jurnal Perempuan dan Anak, 2021)
This study aims to describe the Ecofeminism Movement Through Household Waste Management in the Zona Bening Community, Batu City, East Java. This research uses a descriptive approach with the reason of using narrative nature, so that it can explore all the information from the informants about the activities of the ecofeminism movement through household waste management in the Zona Bening community. The subjects of this research are the core administrators of the Zona Bening community. Data was collected by means of observation, interviews and documentation. The data analysis technique used in this study uses an interactive model which includes data reduction, data display and conclusion drawing. Test the validity of the data using source triangulation techniques. The results of this study indicate that the household waste management activities carried out by the Zona Bening are a manifestation of the ecofeminism movement, this is because the actor who plays a role in the Zona Bening community is a woman who cares about the ecological space. Ecofeminism theory by Vandana Shiva is used as the basis of analysis in this study because the ecofeminism movement is a benchmark that there is awareness that can be shared with the public about the importance of maintaining and preserving the environment that can blend with nature, thus forming harmonization between nature and humans in accordance with the concept of balance.